2007
DOI: 10.1002/ijc.23046
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of cervical neoplasia by Raman spectroscopy

Abstract: Early detection of malignant tumours, or their precursor lesions, improves patient outcome. High risk human papillomavirus (HPV), particularly HPV16, infection can lead to the development of uterine cervical neoplasia, and therefore, the identification in clinical samples of the effects of HPV infection may have clinical value. In this report, we apply Raman microspectroscopy to live and fixed cultured cells to discriminate between defined cell types. Raman spectra were acquired from primary human keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
114
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(117 citation statements)
references
References 20 publications
2
114
0
1
Order By: Relevance
“…With respect to PC3, there is a separation of the CaSki group from the other cell lines and it is important to note that in the PC3 loading there is a distinctive protein peak at 1036cm -1 , 70 which has a clearly different contribution in the CaSki mean spectrum compared to other cell lines (figure 2B and Tyr 44 . Raman and FTIR PCs are dominated by features associated with changes of protein conformation structures; β-sheet, α-helix and disordered structure in PC1, PC2 and PC3, respectively.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…With respect to PC3, there is a separation of the CaSki group from the other cell lines and it is important to note that in the PC3 loading there is a distinctive protein peak at 1036cm -1 , 70 which has a clearly different contribution in the CaSki mean spectrum compared to other cell lines (figure 2B and Tyr 44 . Raman and FTIR PCs are dominated by features associated with changes of protein conformation structures; β-sheet, α-helix and disordered structure in PC1, PC2 and PC3, respectively.…”
mentioning
confidence: 94%
“…In the literature, there is a wide spectrum of experiments concerning cervical 70 cancer investigation with vibrational spectroscopy techniques, demonstrating the usefulness of these methods in understanding cervical cancer progression from the molecular level, and showing its potential application in cervical cancer screening and diagnosis . Raman spectroscopy has also 75 been used to study cell lines derived from the cervix, revealing spectral variations, mostly in peaks originating from DNA and proteins, in cell lines expressing the E7 gene of HPV-16 compared to cells not affected by HPV 44 . Furthermore, a recent study has demonstrated that in low- 5 grade cytology infected with high-risk oncogenic HPV16 or HPV18, it was possible to differentiate samples from women based on whether they were aged 20-29 years vs. 30-39 years using attenuated total reflection infrared spectroscopy 45 .…”
Section: Introductionmentioning
confidence: 99%
“…14 Although Raman spectroscopy is inherently a sensitive technique, previous studies using Raman to detect cervical dysplasia both in vivo and in vitro have reported a wide range of sensitivity (70-100%) and specificity (70-100%) rates. 1,[15][16][17][18][19] Krishna et al used a benchtop Raman spectroscopy system to acquire information from cervical samples ex vivo and classified normal compared to malignant samples at sensitivity and specificity rates of 75-99.5%. 19 Because infection with certain strains of human papillomavirus (HPV) is the cause of cervical dysplasia in >99% of cases worldwide, [20][21][22] certain research groups have used Raman spectroscopy to identify differences between HPV types.…”
Section: Introductionmentioning
confidence: 99%
“…Jess et al used a confocal Raman microscope system and were able to discriminate varying HPV types in live and fixed cells with sensitivity and specificity rates of 70-100%. 15 Our research group has used a portable probe-based Raman spectroscopy system to distinguish between normal and malignant cervical samples in cell culture, in vitro and in vivo. The sensitivity and specificity rates of this work have ranged between 81 and 97%.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the relative intensities of the spectral peaks for SV-HUC-1 and MGH spectra show that urothelial cells (SV-HUC-1) are characterized by relatively strong protein and carbohydrate Raman peaks, in the spectral region 1100 to 1300 cm − 1 , which suggest greater concentrations of proteins and carbohydrates in nonmalignant cells. 23 In contrast, the spectra from bladder cancer cells (MGH) show a significant increase in the peaks pertaining to ring breathing modes in DNA bases, such as 669, 727, 785, 828, 1095, and 1578 cm − 1 , suggesting an increase in the DNA concentration of bladder cancer cells. Tumor cells commonly exhibit an increase in DNA content in the nucleus.…”
Section: Standard and Modulated Raman Spectra For Control Fixed Sv-humentioning
confidence: 98%